Expression and characterization of thermostable glycogen branching enzyme from Geobacillus mahadia Geo-05 - Mohtar, Nur Syazwani; Abdul Rahman, Mohd Basyaruddin; Raja Abd Rahman, Raja Noor Zaliha; Leow, Thean Chor; Salleh, Abu Bakar; Mat Isa, Mohd Noor (PeerJ, 2016)
The glycogen branching enzyme (EC 2.4.1.18), which catalyses the formation of α-1,6-glycosidic branch points in glycogen structure, is often used to enhance the nutritional value and quality of food and beverages. In order to be applicable in industries, enzymes that are stable and active at high temperature are much desired. Using genome mining, the nucleotide sequence of the branching enzyme gene (glgB) was extracted from the Geobacillus mahadia Geo-05 genome sequence provided by the Malaysia Genome Institute. The size of the gene is 2013 bp, and the theoretical molecular weight of the protein is 78.43 kDa. The gene sequence was then used to predict the thermostability, function and the three dimensional structure of the enzyme. The gene was cloned and overexpressed in E. coli to verify the predicted result experimentally. The purified enzyme was used to study the effect of temperature and pH on enzyme activity and stability, and the inhibitory effect by metal ion on enzyme activity. This thermostable glycogen branching enzyme was found to be most active at 55 °C, and the half-life at 60 °C and 70 °C was 24 h and 5 h, respectively. From this research, a thermostable glycogen branching enzyme was successfully isolated from Geobacillus mahadia Geo-05 by genome mining together with molecular biology technique.